OUTCOME OF FRONTLINE TREATMENT WITH “GENERIC” IMATINIB IN ADULT PATIENTS WITH CHRONIC MYELOID LEUKEMIA IN ALGERIAN POPULATION: A MULTICENTER STUDY - Mohamed Amine BEKADJA (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: